TANGGUNG JAWAB AGEN DISTRIBUTOR ATAS PEREDARAN OBAT KUAT IMPORT TANPA IZIN EDAR DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Septyani Roby Hartanty; Susanti Adi Nugroho (Fakultas Hukum Universitas Tarumanagara, 2019)
Law Number 8 of 1999 about Consumer Protection on this matter covers consumer rights and business responsibilities. This study discusses the responsibility for efforts made to fulfill customer rights for information and benefits of imported drugs without marketing permits and also related to licensing regarding permits for consumers who need funds for imported drugs. Legal protection for consumers of illegal drugs carried out by the government through the Food and Drug Supervisory Agency (BPOM). With the presence of BPOM, the government has supervised. Employers are responsible for the makers of goods because they carry out imported goods or official importers. Therefore, businesses that represent individuals must be responsible for losses that arise only as importers not as producers of these goods. Therefore, the legal basis that can be requested by consumers as a form of accountability proposed for drug business assistance is court punishment as regulated by article 62 paragraph 1 of the UUPK. This study gives an appeal to the public to be more careful in taking medicines should be on the advice of a doctor or pharmacist and should not be tempted easily by the promotions offered because drugs containing BKO can be used.